Design of diversion weirs small scale irrigation in hot climates - Baban, Rozgar (Wiley series in water resources engineering, 1995)
Design of Diversion Weirs Small Scale Irrigation in Hot Climates Rozgar Baban In most developing countries, it is now realised that the most important factor in the success of the agricultural sector is the sustainability of irrigation projects. Diversion weirs are the most important components of these projects. The aim of this book is to teach step by step how to design diversion weirs. It encompasses all technical subjects required: site investigation, hydrological, hydraulic and structural analysis. Many numerical examples show how to relate engineering theories to applications. Cover illustration A diversion weir in Tanzania constructed by the farmers with technical assistance from the government.